Salinomycin induces apoptosis and senescence in breast cancer: Upregulation of p21, downregulation of survivin and histone H3 and H4 hyperacetylation - Al Dhaheri, Yusra; Attoub, Samir; Arafat, Kholoud; AbuQamar, Synan; Eid, Ali; Al Faresi, Nesreen; Iratni, Rabah (Biochimica et biophysica acta, 2013)
In the present study, we investigated the effect of Salinomycin on the survival of three human breast cancer cell lines MCF-7, T47D and MDA-MB-231 grown in adherent culture conditions. Cell viability was measured by CellTiter-Glo and Trypan blue exclusion assay. Apoptosis was determined by caspase 3/7 activation, PARP cleavage and Annexin V staining. Cell cycle distribution was assessed by propidium iodide flow cytometry. Senescence was confirmed by measuring the senescence-associated β-galactosidase activity. Changes in protein expression and histone hyperacetylation was determined by western blot and confirmed by immunofluorescence assay. Salinomycinwas able to inhibit the growth of the three cell lines in time- and concentration-dependent manners. We showed that depending on the concentrations used, Salinomycin elicits different effects on theMDA-MB-231 cells. High concentrations of Salinomycin induced a G2 arrest, downregulation of survivin and triggered apoptosis. Interestingly, treatment with low concentrations of Salinomycin induced a transient G1 arrest at earlier time point and G2 arrest at later point and senescence associatedwith enlarged cellmorphology, upregulation of p21 protein, increase in histone H3 and H4 hyperacetylation and expression of SA-β-Gal activity. Furthermore, we found that Salinomycin was able to potentiate the killing of the MCF-7 and MDA-MB-231 cells, by the chemotherapeutic agents, 4-Hydroxytamoxifen and frondoside A, respectively. Our data are the first to link senescence and histone modifications to Salinomycin. This study provides a new insight to better understand the mechanism of action of Salinomycin, at least in breast cancer cells. ► Salinomycin elicits different effects on the MDA-MB 231 cells. ► The magnitude of DNA damage determines the response of the cells to these damages. ► Salinomycin-treated MDA-MB 231cells exhibited markers of senescence. ► Histone H3 and H4 hyperacetylation and elevated expression of the CDK inhibitor, p21 ► Salinomycin potentiates the anticancer activity of frondoside A and 4-hydroxytamoxifen.